问题 解答题
计算:
(1)-
1
3
+5
1
4
-3
1
7
-5
1
4
+12
6
7

(2)3.75-(-
1
2
)+(-4
2
3
)+(-0.5)+(-6
3
4
);
(3)3
2
5
+(-2
7
8
)+(-3
5
12
)+5
3
5
+(-1
1
8
)+5
5
12

(4)(-4
5
8
)+(-3.75)+(-2
3
8
)+(-3
1
4
);
(5)(-123)+3
1
3
+(-4
1
4
)+(+123)+(-
1
3
)+(-
3
4
);
(6)25×
3
4
+(-25)×(-
1
4
);
(7)(-3)2÷2
1
4
×(-
2
3
2+4-22×(-
1
3
);
(8)(-79)÷2
1
4
+
4
9
×(-29);
(9)[30-(
7
9
+
5
6
-
11
12
)×36]÷(-5)
(10)(-1)3-(1-
1
2
)÷3×[3-(-3)2]
(11)(
1
4
+
1
12
-
7
18
-
1
36
)÷
1
36
-2×(-
1
3

(12)-22-(1-
1
5
×0.2)÷(-2)3
(13)99
17
18
×(-9)
(14)-36
9
11
÷9
(15)(-7)×(+5)-90÷(-15)
(16)(-
2
3
)×(-18)-(+0.25)×(-6)÷(-5)
答案

(1)-

1
3
+5
1
4
-5
1
4
-3
1
7
+12
6
7

=-

1
3
+9
5
7

=9

8
21

(2)3.75-(-

1
2
)+(-4
2
3
)+(-0.5)+(-6
3
4

=3.75+

1
2
-4
2
3
-0.5-6
3
4

=3.75-6

3
4
+
1
2
-0.5-4
2
3

=-3-4

2
3

=-7

2
3

(3)3

2
5
+(-2
7
8
)+(-3
5
12
)+5
3
5
+(-1
1
8
)+5
5
12

=3

2
5
+5
3
5
+(-2
7
8
)+(-1
1
8
)+(-3
5
12
)+5
5
12

=9-4+2

=7;

(4)(-4

5
8
)+(-3.75)+(-2
3
8
)+(-3
1
4

=(-4

5
8
)+(-2
3
8
)+(-3
1
4
)+(-3.75)

=-7-7

=-14;

(5)(-123)+3

1
3
+(-4
1
4
)+(+123)+(-
1
3
)+(-
3
4

=(-123)+(+123)+3

1
3
+(-
1
3
)+(-4
1
4
)+(-
3
4

=0+3-5

=-2;

(6)25×

3
4
+(-25)×(-
1
4

=25×(

3
4
+
1
4

=25;

(7)(-3)2÷2

1
4
×(-
2
3
2+4-22×(-
1
3
);

=9×

4
9
×
4
9
+4-4×(-
1
3

=

16
9
+4+
4
3

=

64
9

(8)(-79)÷2

1
4
+
4
9
×(-29)

=(-79)×

4
9
+
4
9
×(-29)

=(-79-29)×

4
9

=-108×

4
9

=-48;

(9)[30-(

7
9
+
5
6
-
11
12
)×36]÷(-5)

=[30-(

7
9
×36+
5
6
×36-
11
12
×36)]÷(-5)

=[30-28-30+33]÷(-5)

=5÷(-5)

=-1;

(10)(-1)3-(1-

1
2
)÷3×[3-(-3)2]

=-1-

1
2
×
1
3
×[3-9]

=-1-

1
2
×
1
3
×[3-6]

=-1+1

=0;

(11)(

1
4
+
1
12
-
7
18
-
1
36
)÷
1
36
-2×(-
1
3

=(

1
4
+
1
12
-
7
18
-
1
36
)×36+
2
3

=

1
4
×36+
1
12
×36-
7
18
×36-
1
36
×36+
2
3

=9+3-14-1+

2
3

=-

7
3

(12)-22-(1-

1
5
×0.2)÷(-2)3

=-22-(1-

1
25
)÷(-8)

=-22-

24
25
×(-
1
8

=-22+

3
25

=-21

22
25

(13)99

17
18
×(-9)

=(100-

1
18
)×(-9)

=100×(-9)-

1
18
×(-9)

=-900+

1
2

=-899

1
2

(14)-36

9
11
÷9

=-36×

1
9
-
9
11
×
1
9

=-4

1
11

(15)(-7)×(+5)-90÷(-15)

=-35+6

=-29;

(16)(-

2
3
)×(-18)-(+0.25)×(-6)÷(-5)

=12-(-1.5)÷(-5)

=12-0.3

=11.7.

单项选择题
问答题 简答题